Personality and Mind-Wandering Self-Perception: The Role of Meta-Awareness - Ibaceta, Miguel; Madrid, Hector P. (Frontiers in Psychology, 2021)
Mind-wandering is a psychological process involving the emergence of spontaneous thoughts in daily life. Research has shown that mind-wandering influences diverse psychological outcomes; however, less is known about possible individual differences that may drive mind-wandering. In this study, we argue that personality traits, expressed in neuroticism and openness to experience, may lead to the individual’s self-perception of their mind-wandering activity, due to meta-awareness processes. In a three-wave survey study with 273 college students, we gathered data which supported a positive association of both neuroticism and openness to experience with mind-wandering self-perception, mediated by the individual’s meta-awareness. Thus, this study contributes to the literature on spontaneous thinking by showing that mind-wandering processes may be a function of individual differences expressed in personality traits.